Understanding the Barriers of Implementing a Self-Awareness Assessment in Occupational Therapy Practice within a Brain Injury Population: An Exploratory Study - Anika Cheng; Rebecca Tsow; Julia Schmidt (Occupational Therapy International)
Background. Self-awareness is seldom formally assessed by occupational therapists among individuals with traumatic brain injury (TBI). However, impaired self-awareness is prevalent and has a significant impact on rehabilitation outcomes. There is a need to understand clinician perspectives on self-awareness assessments and promote evidence-based practice in clinical settings. Aims. (1) Explore how an education session impacts knowledge and use of self-awareness assessments in occupational therapists working with people with TBI; (2) Understand the barriers that occupational therapists experience when assessing self-awareness in clinical practice. Materials and Methods. A single-group pre-post session design with an integrated knowledge translation approach was used. Occupational therapists working in neurorehabilitation were recruited from two rehabilitation centres through convenience sampling. Participants completed questionnaires before, after, and three months following an education session about the Self-Awareness of Deficits (SADI) assessment. Results. 14 occupational therapists participated in this study. A statistically significant increase in knowledge and confidence in using the SADI was observed both post-session and at 3-month follow-up. Conclusion. Targeted and ongoing education promotes confidence and knowledge retention among occupational therapists. Further research should explore strategies to promote behaviour change. Significance. The barriers identified in this study can provide insights for knowledge translation across clinical contexts.